Genetic studies of Prader-Willi patients from Taiwan identify two patients with atypical deletions and provide evidences for conservation of genomic architecture in proximal chromosome 15q - Lin, Shuan Pei. (2011)
Prader-Willi syndrome (PWS) is a neurogenetic disorder associated with recurrent genomic recombination involving low copy repeats (LCRs) located in the human chromosome 15q11-q13. Previous studies of PWS patients from Asia suggested that there is a higher incidence of deletion and lower incidence of maternal uniparental